(untitled) - Zengage, Thomas R. (Hong Kong, 1988)
Thomas Zengage, one of the authors of this book, is a managing vice president of the seventh-largest consulting company in the world, which he runs out of his small Tokyo office. He boldly predicted in this book--which was written about 1990--that major Japanese companies and Japan Inc. would increasingly dominate the global business community. The book is full of similar insights, and was way ahead of its time, or perhaps behind its time, depending on how you look at it. Simply written, I would recommend it for a long weekend at the beach.
Keywords: International finance,Economic history,Tài chính quốc tế,Lịch sử kinh tế